Chromosomal Abnormalities and Pregnancy Outcomes for Fetuses With Gastrointestinal Tract Obstructions - Wu, Xiaoqing; Su, Linjuan; Shen, Qingmei; Guo, Qun; Li, Ying; Xu, Shiyi; Lin, Na; Huang, Hailong; Xu, Liangpu (Frontiers in Pediatrics, 2022)
Fetal gastrointestinal tract obstruction (GITO) is the most frequently encountered gastrointestinal defect in the prenatal period. This study aimed to investigate the genetic disorders and pregnancy outcomes of fetal GITO. We reviewed data from 70 pregnancies that were referred for invasive prenatal testing because of fetal GITO. According to the level of obstruction, they were classified into esophageal atresia/stenosis, duodenal atresia/stenosis, jejunal or ileal atresia/stenosis, or anal atresia. Traditional karyotyping was performed on all the 70 pregnancies, and chromosomal microarray analysis (CMA) was performed on 32 of them in parallel. Traditional karyotyping revealed twelve (17.1%) chromosomal abnormalities, including 11 cases of trisomy 21 (Down syndrome), and one case of a supernumerary marker chromosome related to Cat eye syndrome. According to the absence or presence of other ultrasound anomalies, they were categorized into isolated GITO (n = 36) and non-isolated GITO (n = 34). The rate of chromosomal abnormalities in the non-isolated GITO pregnancies was significantly higher than that in the isolated GITO pregnancies (29.4 vs. 5.5%, p < 0.05); the survival rate in the isolated group was significantly higher than that in the non-isolated group (67.6 vs. 34.4%, p < 0.05). Among the 32 cases where CMA was performed, an additional one (3.1%) copy number variant with clinical significance was noted in a fetus with normal karyotype. The microduplication on 7q12 was considered to be the genetic etiology of duodenal stenosis, although it was inherited from a phenotypically normal mother. Our study supports the strong association between Down syndrome and fetal GITO, especially duodenal stenosis. Our findings suggested that the risk of chromosomal abnormalities was increased when GITO was accompanied by other ultrasound anomalies; thus, chromosomal abnormalities and fetal anatomy should be carefully evaluated for pregnancy management of fetal GITO.